Cloning, Characterization, and Expression Analysis of the Vasa Gene from Kryptolebias marmoratus - Perry, Jacob Lance (My University, 2013)
Kryptolebias marmoratus, formerly known as the Mangrove Rivulus, has been studied in the laboratory setting since the late 1950s. K. marmoratus is a selfing hermaphrodite with a unique gonad, termed the ovotestis, consisting of both ovarian and sperm tissue. One particular gene of interest to the development of this gonad is the vasagene. Vasa is an ATP-dependent RNA helicase, which has been studied in many different organisms such as: Drosophila melanogaster (fruit fly), Homo sapiens (humans), Ambystoma mexicanum (salamander), Xenopus laevis (frog), Danio rerio (zebrafish), Oryzias latipes (medaka), and Strongylocentrotus purpuratus (sea urchin). The vasa gene was cloned and sequenced from K. marmoratus. The gene consists of 2,273 nucleotides, a predicted amino acid sequence of 641 base pairs, and a 3 ' untranslated region (UTR) of 234 base pairs in length. BLASTp and phylogenetic analysis revealed that the kmvasa gene is closely related to T oreintalis (Pacific blue fin tuna) and has a close relationship to 0. latipes (medaka). The ATP-dependent RNA helicase vasa protein was detected in only the gonad region of K. marmoratus hermaphrodites and males. In other species, the vasa protein is detected throughout embryogenesis. It was successfully shown that the K. marmoratus vasa gene is also expressed at similar levels throughout embryogenesis.
Jacob Lance Perry M.S. in Biology, 2012. Valdosta State University.
Keywords: ovotestis; vasa ATP-dependent RNA helicase; UTR; phylogenetic analysis; QPCR